2022
DOI: 10.1111/evj.13562
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic changes of the proximal third metatarsal bone do not predict presence or severity of proximal suspensory desmopathy in a predominately Quarter Horse population

Abstract: Background: Comparison of radiography to magnetic resonance imaging (MRI) can help objectively assess the value and limitations of radiographs in orthopaedic disease processes. The tarsus and proximal suspensory origin of the metatarsus are commonly imaged regions for lameness. The knowledge gained by comparison between imaging modalities will aid in improving accuracy of radiographic interpretation.Objective: To compare the radiographic and MRI findings of the proximal third metatarsal bone (MTIII) and proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…43 MRI is more sensitive for detection and characterization of lesions of the suspensory ligament, and its bony origin as compared with radiography and ultrasonography. 1,3,44,[103][104][105][106] There is good correlation of suspensory ligament lesion detection with MRI and histopathology. 103 Bone marrow lesions, sclerosis, resorption, and enthesophyte formation within the metacarpal or third metacarpal bone associated with the origin of the ligament can be readily identified in addition to pathology within the ligament itself, including enlargement, irregular margins, and abnormal signal intensity patterns.…”
Section: Proximal Metacarpus/metatarsus and Carpal/tarsal Regionsmentioning
confidence: 98%
“…43 MRI is more sensitive for detection and characterization of lesions of the suspensory ligament, and its bony origin as compared with radiography and ultrasonography. 1,3,44,[103][104][105][106] There is good correlation of suspensory ligament lesion detection with MRI and histopathology. 103 Bone marrow lesions, sclerosis, resorption, and enthesophyte formation within the metacarpal or third metacarpal bone associated with the origin of the ligament can be readily identified in addition to pathology within the ligament itself, including enlargement, irregular margins, and abnormal signal intensity patterns.…”
Section: Proximal Metacarpus/metatarsus and Carpal/tarsal Regionsmentioning
confidence: 98%
“…For performing this retrospective, observational, controlled study, CT and radiographic assessment of the PSL (Supporting Information S1). 6,8,11,12 The analysis of bone (B) and soft tissue window (ST) CT image series included the severity (grade 0-3) and localization of PSL findings (2/4/6 cm) with an evaluation of the following categories (Supporting Information S1):…”
Section: Selection and Description Of Subjectsmentioning
confidence: 99%
“…[1][2][3] The pathology is characterized by a varying combination of osseous changes at the proximoplantar metatarsus III (MTIII), enthesopathy, and desmopathy of the suspensory origin that may cause local nerve compression. [4][5][6] The diagnosis of PSD is generally based on regional analgesia and diagnostic imaging including ultrasonography and radiography. 5,7,8 It has, however, been shown that the majority of ultrasonographic measurements are not very precise and radiographic changes do not reliably predict the presence or severity of PSD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this retrospective observational study by Frances Hinkle and co‐workers at Colorado State University , USA , was to compare the radiographic and MRI findings of the proximal third metatarsal bone (MtIII) and proximal suspensory ligament , using MRI as the gold standard .…”
Section: Radiographic Findings Of the Mtiiimentioning
confidence: 99%